Diagnostic Immunohistochemistry for Soft Tissue and Bone Tumors: An Update. (November 2018) - Schaefer, Inga-Marie; Hornick, Jason L.
Abstract : Although some soft tissue and bone tumors can be identified based on histologic features alone, immunohistochemistry plays a critical diagnostic role for most mesenchymal tumor types. The discovery of recurrent genomic alterations in many benign and malignant mesenchymal neoplasms has added important biologic insights and expanded the spectrum of some diagnostic subgroups. Some tumors are defined by unique genomic alterations, whereas others share abnormalities that are not tumor-specific and can be observed in a sometimes broad range of biologically unrelated neoplasms. We herein focus on novel immunohistochemical markers, based on molecular genetic alterations, which are particularly useful in the diagnostic workup of selected groups of soft tissue and bone tumors, including recently described entities, specifically round cell sarcomas (Ewing sarcoma, CIC -rearranged sarcoma, and BCOR -rearranged sarcoma), vascular tumors (epithelioid hemangioma, epithelioid hemangioendothelioma, and pseudomyogenic hemangioendothelioma), SMARCB1-deficient neoplasms, adipocytic tumors (spindle cell/pleomorphic lipoma, atypical spindle cell lipomatous tumor, and conventional atypical lipomatous tumor), giant cell-rich bone tumors (giant cell tumor of bone and chondroblastoma), and biphenotypic sinonasal sarcoma. Given the complex nature of sarcoma classification, and the rarity of many mesenchymal tumor types, careful integration of clinical presentation, imaging features, histology, immunophenotype, and cytogenetic/molecular alterations is crucial for accurate diagnosis of soft tissue and bone tumors.